PRESUPPOSITION IN GITASAV PODCAST - cindy, audylia herawati; CINDY, CINDY QURROTUL A'YUN (Universitas Negeri Surabaya, 2025)
This study explores the cultural norms embedded in presuppositions in Gita Savitri’s “Childfree Podcast” through a pragmatic lens. The research addresses the issue of how cultural and societal expectations surrounding parenthood are reflected in the podcast’s discourse, particularly through the use of presupposition. The aim of this study is to unpack these cultural norms and understand their role in shaping attitudes towards the childfree choice. A qualitative approach was used to analyze the language of the podcast, focusing on the presuppositions conveyed by the speaker. The analysis revealed that Gita Savitri uses presuppositions to challenge conventional norms related to parenthood, subtly promoting the childfree lifestyle. The findings suggest that presupposition is a powerful tool in discourse, influencing listeners' perceptions and contributing to the normalization of non-traditional family structures. This study concludes that podcasts like Gita Savitri's play a significant role in reshaping societal values regarding parenthood.